Lipid effects of sodium-glucose cotransporter 2 inhibitors. Issue 3 (June 2021) - Lazarte, Julieta; Kanagalingam, Tharsan; Hegele, Robert A.
Abstract : Purpose of review: Sodium-glucose cotransporter 2 (SGLT2) inhibitors are widely used antihyperglycemic drugs that show remarkable cardiorenal protective effects in patients with or without type 2 diabetes. Furthermore, they are effective among patients across a wide range of baseline renal and cardiac function. Numerous mechanisms have been evaluated to understand these remarkable clinical benefits. From an early stage, these agents were noted to affect the plasma lipid profile. Here we review lipid profile alterations attributable to SGLT2 inhibitors and also some mechanisms explored in model systems and human studies. Recent findings: SGLT2 inhibitors given to patients with diabetes as monotherapy shift substrate utilization from carbohydrates to lipids, and have mild effects on the lipid profile. Increased LDL cholesterol appears to be associated with increased hepatic production and decreased catabolism. Increased HDL cholesterol and decreased triglycerides appear to be associated with improved insulin sensitivity and increased lipolysis. Lipid effects of SGLT2 inhibitors are further modulated by background therapy with other diabetes medications and statins. Summary: The minor lipid profile alterations observed in patients treated with SGLT2 inhibitors are offset by the staggering range of beneficial pleiotropic mechanisms that likely explain the marked cardiorenal benefits of these agents.